42.3k views
0 votes
Solve for f.
-f + 2 + 4f = 8 - 3f

2 Answers

5 votes

-f +2+4f = 8-3f

3f+2 = 8-3f

6f = 6

f = 1

User Daniel McLaury
by
5.0k points
2 votes

Answer:

f = 1

Explanation:

Isolate the variable, f. Note the equal sign, what you do to one side, you do to the other.

Add 3f and subtract 2 from both sides:

-f + 2 (-2) + 4f (+3f) = 8 (-2) - 3f (+3f)

-f + 4f + 3f = 8 - 2

Simplify:

(-f + 7f) = 6

7f - f = 6

6f = 6

Isolate the variable, f. Divide 6 from both sides:

(6f)/6 = (6)/6

f = 6/6

f = 1

1 is your answer for f.

~

User Mora
by
4.9k points